Irreparable Breach or Late-Medieval Reform? Luther’s Address to the Christian Nobility and the Conciliar Reform Tradition - Serina, Richard J. (Reformation & Renaissance review, 2020)
Martin Luther’s 1520 reform treatise, Address to the Christian Nobility, notably pleaded to secular authorities to help reform the German territorial churches of the Empire. Treatments of the Address, however, have neither explained adequately the source of Luther’s proposals nor taken into account recent scholarship on late-medieval conciliar reform and its aspirations to undertake wide-ranging disciplinary improvements. This study compares three specific reforms in Luther’s treatise (annates and services, Roman curia, and papal provisions and reservations) with their analogues at the councils of Constance (1414-1418) and Basel (1431-1449) to show the overlap between them. It will emerge that while Luther likely inherited the proposals from the German Gravamina, he was not aware of the conciliar reforms mediated through those Gravamina, or of the fact that the territorial authorities to which he appeals in his treatise were largely responsible for the failure of those conciliar efforts.